2002
DOI: 10.2188/jea.12.424
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Risk Factors for Development of Type 2 Diabetes: Emphasis on Physical Activity.

Abstract: The aim of this case-control study was to evaluate the association between the lifestyle risk factors, especially physical activity, and the prevalence of type 2 diabetes and the comorbidity of type 2 diabetes and dyslipidemia in middle-aged Japanese urban population. Subjects (279 males and 119 females, 53.5+/-6.8 years old) were selected from one city office in Tokyo and consisted of type 2 diabetes cases (n=53), dyslipidemia cases (n=130), the comorbidity cases (n=58) and sex- and age-matched controls (n=15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Physical activity has been associated to a reduced risk for excessive weight gain, insulin resistance and type 2 diabetes mellitus 65,66,67 . Few studies evaluated the association between physical activity and gestational diabetes mellitus, however it has been stated that increasing physical activity could decrease the glucose intolerance in diabetic pregnant women 68 .…”
Section: Physical Activitymentioning
confidence: 99%
“…Physical activity has been associated to a reduced risk for excessive weight gain, insulin resistance and type 2 diabetes mellitus 65,66,67 . Few studies evaluated the association between physical activity and gestational diabetes mellitus, however it has been stated that increasing physical activity could decrease the glucose intolerance in diabetic pregnant women 68 .…”
Section: Physical Activitymentioning
confidence: 99%
“…Wang et al (11) concluded that there is a relationship between physical activity (PA) and reduced risk of type 2 diabetes mellitus. Therefore, inactivity, especially watching television for long durations, increases the risk of diabetes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Another risk factor of diabetes is the lack of physical activity. Previous studies have shown that high levels of physical activity are associated with reduced risk of diabetes [60][61][62][63]. However, about 46% of primary care patients at risk for diabetes did not do physical activity per week [40]; while two-third of patients with diabetes remain inactive [64].…”
Section: Discussionmentioning
confidence: 99%